STRUCTURE OF SOIL FOOD WEB IN SMALLHOLDER COCOA PLANTATION, SOUTH KONAWE DISTRICT, SOUTHEAST SULAWESI, INDONESIA - Kilowasid, Laode Muhammad Harjoni; Syamsudin, Tati Suryati; Sulystiawati, Endah; Susilo, Fransiscus-Xaverius (AGRIVITA Journal of Agricultural Science, 2014)
An understanding of the structure of the soil food web is critical in determining the practices of soil fertility management based on the biological processes in tropical agricultural regions. The objectives of the study were to assess the variation in trophic level biomass and to analyze the dynamics of the energy channels on the increasing age of cocoa plantation. The characteristics of soil food web structure in smallholder cocoa plantation aged 4, 5, 7, 10, and 16 years were analyzed. The results showed that only biomass at the third trophic level increased with plantation age, but not for the biomass at the lower trophic levels. Biomass in all energy channels did not increased as well along with plantation age. We concluded that variation in the soil food web structure was more influenced by biotic factors of macro-arthropods group, such as facilitation, recolonization capabilities and accessibility in the soil habitat of smallholder cocoa plantation. Keyword: biomass, biotic, energy channel, trophic level.